Comparison of the Efficacy of Three Different Mouthrinse Solutions in Decreasing the Level of Streptococcus Mutans in Saliva - Kocak, Mustafa Murat; Ozcan, Suat; Kocak, Sibel; Topuz, Ozgur; Erten, Hulya (European Journal of Dentistry, 2009)
Objectives: The aim of this study was to evaluate the effectiveness of three different antiseptic mouthrinse solutions on the saliva samples obtained from the individuals, who had high caries activity rate.Methods: The efficacy of three antiseptic mouthrinses were evaluated in a study with healthy volunteers. The three antiseptic solutions used in this study were 0.1% octenidine dihydrochloride (Octenisept, Schülke&Mayr, UK), 0.12% chlorhexidine digluconate (Kloroben, Drogsan, Turkey) and an antimicrobial enzymatic rinse (Biotene, Laclede,Inc, USA). A total of 27 adult volunteer subjects were participated in the study. The subjects were stratified into three balanced group. Then the mouth rinses were used by each group according to the manufacturers directions. The subjects were restricted for 60 minutes for food intake after using the prescribed mouthrinse. The saliva samples were collected from the volunteers at 1, 10 and 60 minutes after their usage in tubes. The tubes were kept in +4°C in a fridge till the evaluation. 10-3 and 10-5 dilutions were prepared for each solution and S. mutans were evaluated according to total number of colony forming unit (CFU) per ml. The dilutions were spreaded on the surface of Brucella agar plates for anaerobic incubation for 48 hours. The dilutions were 100, 10-3 and 10-5 of the solutions Kloroben, Biotene, Octenisept, and the time factor were 0, 1, 10 and 60 minutes. The statistical analyses were performed by Duncan and Bonferroni tests.Results: Octenisept was found to be more effective over S. mutans than the other mouthrinse solutions (P<.05).Conclusions: All mouthrinse solutions except Biotene were effective on oral microorganisms. (Eur J Dent 2009;3:57-61)
Keywords: Mouthrinse solutions; Saliva; S. mutans